2020
DOI: 10.3389/fimmu.2020.01204
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia Reperfusion Injury Triggers CXCL13 Release and B-Cell Recruitment After Allogenic Kidney Transplantation

Abstract: Ischemia reperfusion injury (IRI) is linked with inflammation in kidney transplantation (ktx). The chemokine CXCL13, also known as B lymphocyte chemoattractant, mediates recruitment of B cells within follicles of lymphoid tissues and has recently been identified as a biomarker for acute kidney allograft rejection. The goal of this study was to explore whether IRI contributes to the up-regulation of CXCL13 levels in ktx. It is demonstrated that systemic levels of CXCL13 were increased in mouse models of uni-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…After reperfusion, the microvascular injury caused by ischemia enhances fluid filtration, with leukocyte plugging in capillaries and damaged endothelial cells secreting factors to favor inflammatory mediators and proteolytic enzymes ( 146 ). The global outcome of this ischemia-reperfusion damage is a harmful environment that through DAMPS and PAMPS enhances both innate and cellular immunity ( 147 ).…”
Section: The Harmsmentioning
confidence: 99%
“…After reperfusion, the microvascular injury caused by ischemia enhances fluid filtration, with leukocyte plugging in capillaries and damaged endothelial cells secreting factors to favor inflammatory mediators and proteolytic enzymes ( 146 ). The global outcome of this ischemia-reperfusion damage is a harmful environment that through DAMPS and PAMPS enhances both innate and cellular immunity ( 147 ).…”
Section: The Harmsmentioning
confidence: 99%
“…Additionally, renal grafts inevitably experience ischemia as soon as they are removed from the donor. IRI is a well-known risk factor for the development of delayed graft function [ 22 , 23 ]. Although most renal graft transplant recipients can completely recover from the initial period, clinical evidence has demonstrated that transplanted kidneys with prolonged ischemic periods are more susceptible to long-term deterioration [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the infiltration levels of activated B cells and immature B cells were higher in the high CPC score group, suggesting a potential connection between the level of B-cell infiltration and the outcome in patients with CA. Previously, the study by Kreimann et al showed that ischemia/reperfusion injury after allogeneic renal transplantation triggers CXCL13 release and B-cell recruitment [ 41 ]. In addition, the study by Renner et al showed that B-cell subsets contribute to renal injury and renal protection after ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%